Study on Damping Energy Dissipation Characteristics of Cylindrical Metal Rubber in Nonforming Direction - Zhi Ying Ren; Qisheng Chen; Hongbai Bai; Yiwan Wu (Advances in Materials Science and Engineering)
Metal rubber (MR) is an excellent damping material that is often used in practical engineering applications. The performance of MR in the nonforming direction is different from that in the molding direction, and research is rare; the anisotropy of MR is gradually revealed in many engineering applications because characterization and analysis of damping energy dissipation characteristics in the nonforming direction of cylindrical MR were carried out by the characterization method of damping materials. Based on the testing methods, dry friction and dynamic stiffness are taken as the main analysis points. By performing single-factor control and orthogonal tests, the parameters affecting the energy dissipation and damping characteristics of MR are studied, and the main factors that cause changes in energy consumption and loss factor are analyzed. It is found that the influence of loading amplitude on damping energy is much higher than that of loading frequency, and the damping characteristic of MR is not sensitive to frequency. Therefore, the loading amplitude level of the actual environment should be considered first followed by the knitting technology in design of MR components.